Efficacy of simplified-cognitive behavioral therapy for insomnia(S-CBTI) among female COVID-19 patients with insomnia symptom in Wuhan mobile cabin hospital - He, Jin (Sleep Breath, 2021)
BACKGROUND: The outbreak of Coronavirus Disease-2019 (COVID-19) caused great psychological distress often with comorbid insomnia. Insomnia is common in patients with COVID-19 admitted to mobile cabin hospitals. Insomnia may lead to immune dysfunction, a condition not conducive to recovery from COVID-19. The use of sedative-hypnotic drugs is limited by their inhibitory effect on the respiratory system. A paucity of research is available regarding psychotherapy interventions to improve insomnia symptoms among  patients with COVID-19. In the general population, sleep problems are more common in women than in men; insomnia in women patients requires special attention. The aim of this study was to develop simplified-cognitive behavioral therapy for insomnia (S-CBTI) for patients with COVID-19 and comorbid insomnia symptoms and to verify its effectiveness through a self-control trial. A second aim was to compare the effectiveness of S-CBTI between acute and chronic insomnia among women with COVID-19 and comorbid insomnia symptoms in Wuhan Jianghan Cabin Hospital. METHODS: S-CBTI consisted of education on COVID-19 and sleep hygiene, stimulus control, sleep restriction, and self-suggestion relaxation training over a period of two consecutive weeks. Of 67 women, 66 completed psychological intervention and baseline and post-intervention assessments. There were 31 women with acute insomnia and 35 with chronic insomnia. The Insomnia Severity Index (ISI) score and self-compiled sleep data were assessed at baseline and post-intervention, and subjective sleep evaluations were assessed at days 4, 7, 12, and 14. RESULTS: The ISI score, sleep latency, night sleep time, and sleep efficiency were statistically significantlly improved from baseline to post-intervention by paired T-test. After the intervention, the mean ISI score of the acute insomnia group was lower than that of the chronic insomnia group. The reduction of the ISI score and the improvement of sleep time from baseline to post-intervention in the acute insomnia group were greater than those in the chronic insomnia group. Utilization of sedative-hypnotic drugs in the acute insomnia group was less than that in the chronic insomnia group, and the difference was statistically significant. CONCLUSIONS: S-CBTI can improve the insomnia symptoms of women with COVID-19 in mobile cabin hospitals, especially for stress-related acute insomnia.